A School for the Lord's Service: Norwich Cathedral and the recovery of a Benedictine Heritage - Doll, Peter (2025)
In the mediaeval Church in England, half of the diocesan cathedrals were also monastic communities; this phenomenon was virtually unique in the Church worldwide. Even after the Reformation, the monastic character of cathedrals continued to have a profound influence on the liturgy of the Church of England and on cathedrals as places to maintain the daily worship of God in solemn and musical form; to be homes for libraries and scholarship, and to be places of retreat and contemplative prayer. Norwich Cathedral was the last of these monastic cathedrals to be established (1096) and the first of the monastic cathedrals to be dissolved (1538). Particularly since the mid-nineteenth century, it has self-consciously been recovering a Benedictine character to its mission and ministry, most recently in the reconstruction of three monastic buildings lost since the Reformation: the Library reading room, the Refectory, and the Hostry. These buildings, while modern in design, build upon the remaining monastic fabric and echo the proportions and materials of their monastic predecessors, exemplifying the monastic vows of stability, obedience, and conversion of life. The Cathedral’s Benedictine principles extend to its ethos as an employer and commercial enterprise.